Intestinal Parasitic Infestation among the Outdoor Patients of Dhaka University Medical Centre, Bangladesh - Khanum, Hamida; Rahman, Md Mizanur; Uddin, Md Hafiz; Alam, Shahela; Rahman, Fatema; Farhana, Rimi (University Journal of Zoology, Rajshahi University, 2010)
In the present study, the prevalence of intestinal parasitic infestation was investigated among the outdoor patients including teacher, student and staff of the Dhaka University treated at Dhaka University Medical Centre. A total of 380 stool samples were examined. Four species of intestinal parasites were identified, two protozoans (Entamoeba histolytica and Giardia intestinalis) and two nematodes (Ascaris lumbricoides and Trichuris trichiura). The prevalence of parasitic infestation was 24.73%. The prevalence of E. histolytica was 3.95%, G. intestinalis 6.31%, A. lumbricoides 11.84% and T. trichiura 2.63%. The prevalence was higher in case of staff (32.31%) and lower in case of teacher (13.16%). Highest prevalence observed during the rainy season (29.3%) and lowest in winter (19.4%). Female patient showed higher prevalence (31.25%) compared to male (24.14%). The rate of infection was higher (28.3%) among the patients, who used to drink unboiled water. The present study revealed that parasitic infection among the outdoor patients of Dhaka University Medical Centre is alarmingly high. Key words: Dhaka University Medical Centre; intestinal parasites; outdoor patients DOI: 10.3329/ujzru.v28i0.5285 Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 45-49